Evaluation and Prevention of Water Damage to Asphalt Pavement Materials 1985
DOI: 10.1520/stp35325s
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Asphalt Concrete Durability Resulting from Exposure to Multiple Cycles of Freezing and Thawing

Abstract: Concern over water-induced damage in asphalt concrete pavements has resulted in the development of several new moisture susceptibility detection tests. This report compares two modifications of the water conditioning procedure for asphalt concrete specimens as described in the National Cooperative Highway Research Program (NCHRP) Reports 192 and 246. These modifications incorporate longer water exposure conditions for investigating the long-term durability of antistripping additives and paving mixtures. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…In addition, the ambient conditions (including temperature, freeze -thaw cycles and wetting -drying cycles) can also significantly affect the durability of an asphalt pavement material (Gilmore et al 1985, Huang et al 2005.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the ambient conditions (including temperature, freeze -thaw cycles and wetting -drying cycles) can also significantly affect the durability of an asphalt pavement material (Gilmore et al 1985, Huang et al 2005.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have indicated that the susceptibility of asphalt mixtures to moisture attack is related to the bitumen chemistry, aggregate mineralogy, surface texture of the aggregate and the adhesion between the bitumen binder and the aggregates [3,[6][7][8][9]. In addition, the ambient conditions (including temperature, freeze-thaw cycles and wetting-drying cycles) can also affect significantly the durability of an asphalt road-pavement material [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…And the increase in the number of potholes due to natural causes (e.g., due to weather conditions) is arguably exogenous to digital public engagement other than reporting potholes. The engineering and material science literature (Gilmore et al 1985;Guo et al 2018) identifies the frequency of freeze-soak-scour cycles in the spring-thawing season as the main cause of pavement damage in the areas affected by winter frost. Moscow's geographical location and exposure to harsh winters make the city an ideal case for this particular factor affecting local road quality.…”
Section: Appendix Tablementioning
confidence: 99%